2020
DOI: 10.1016/j.idcr.2020.e00959
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatic injury induced by COVID-19

Abstract: We report a patient with COVID-19 infection presenting with acute pancreatitis. The diagnosis of pancreatitis was based on laboratory as well as radiological evidence, and all the usual etiologies were ruled out. The temporal association with COVID-19 is strongly suggestive of novel coronavirus induced pancreatic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Patnaik et al [ 39 ] described the case of a 29-year-old man with abdominal pain radiating to the back and dyspnea for 5 d. Laboratory tests revealed leukocytosis, hyperamylasemia, and hyperlipasemia. CT showed that the pancreas was swollen.…”
Section: Case Reports and Cohort Studies On Ap In Covid-19 In The Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Patnaik et al [ 39 ] described the case of a 29-year-old man with abdominal pain radiating to the back and dyspnea for 5 d. Laboratory tests revealed leukocytosis, hyperamylasemia, and hyperlipasemia. CT showed that the pancreas was swollen.…”
Section: Case Reports and Cohort Studies On Ap In Covid-19 In The Literature Searchmentioning
confidence: 99%
“…Conservative treatment using meropenem was administered. After several days, his clinical state was improved, and he was discharged[ 39 ].…”
Section: Case Reports and Cohort Studies On Ap In Covid-19 In The Literature Searchmentioning
confidence: 99%
“…Studies have suggested a causal relationship between SARS-CoV-2 infection and acute pancreatitis (17,18). Pancreatic injury may emerge directly due to viral replications, or it may be due to in ammatory processes and immune dysregulation caused by COVID-19 (12,(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…In the reviewed studies, pancreatic enzyme levels were detected from normal (27) to above 20 to 30 times more than the normal range (19,28). In addition to that, the C-Reactive Protein (CRP) level also was up to 20-times elevated (17).…”
Section: Diagnosismentioning
confidence: 97%
“…Despite this, little attention has been paid to the extent and details of pancreatic injury caused by COVID-19[ 53 ]. Fortunately, so far, an increasing number of studies have reported pancreatic injury in patients with COVID-19 infection, which received the attention of clinicians and researchers[ 57 - 62 ]. Combined with clinical data, Liu et al [ 53 ] showed that 1%-2% of non-severe and 17% of severe patients with COVID-19 had pancreatic injury.…”
Section: Digestive System Manifestations In Covid-19 Patientsmentioning
confidence: 99%